2016
DOI: 10.1007/s00442-016-3630-5
|View full text |Cite
|
Sign up to set email alerts
|

Staying cool in a changing landscape: the influence of maximum daily ambient temperature on grizzly bear habitat selection

Abstract: To fulfill their needs, animals are constantly making trade-offs among limiting factors. Although there is growing evidence about the impact of ambient temperature on habitat selection in mammals, the role of environmental conditions and thermoregulation on apex predators is poorly understood. Our objective was to investigate the influence of ambient temperature on habitat selection patterns of grizzly bears in the managed landscape of Alberta, Canada. Grizzly bear habitat selection followed a daily and season… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 74 publications
1
34
1
Order By: Relevance
“…Fine‐scale climatic measurements can help identify thermal refuges overlooked by large‐scale modelling approaches, but an organism's size, mobility and perceptions will influence the scale or scales at which individuals respond to the thermal landscape (Hannah et al., ; Kotliar & Wiens, ). For example, Landsat imagery (30‐m resolution) has been used to estimate values of habitat structure in evaluations of thermal quality for moose Alces alces (Olson, Windels, Fulton, & Moen, ) and grizzly bears Ursos arctos (Pigeon, Cardinal, Stenhouse, & Cȏté, ), but such large‐bodied and mobile organisms perceive thermal heterogeneity differently than smaller species. Our results reveal that even modest changes in habitat structure can result in attenuated thermal environments across small spatial scales.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fine‐scale climatic measurements can help identify thermal refuges overlooked by large‐scale modelling approaches, but an organism's size, mobility and perceptions will influence the scale or scales at which individuals respond to the thermal landscape (Hannah et al., ; Kotliar & Wiens, ). For example, Landsat imagery (30‐m resolution) has been used to estimate values of habitat structure in evaluations of thermal quality for moose Alces alces (Olson, Windels, Fulton, & Moen, ) and grizzly bears Ursos arctos (Pigeon, Cardinal, Stenhouse, & Cȏté, ), but such large‐bodied and mobile organisms perceive thermal heterogeneity differently than smaller species. Our results reveal that even modest changes in habitat structure can result in attenuated thermal environments across small spatial scales.…”
Section: Discussionmentioning
confidence: 99%
“…Fine-scale climatic measurements can help identify thermal refuges overlooked by largescale modelling approaches, but an organism's size, mobility and perceptions will influence the scale or scales at which individuals respond to the thermal landscape (Hannah et al, 2014;Kotliar & Wiens, 1990). For example, Landsat imagery (30-m resolution) has been used to estimate values of habitat structure in evaluations of thermal quality for moose Alces alces (Olson, Windels, Fulton, & Moen, 2014) and grizzly bears Ursos arctos (Pigeon, Cardinal, Stenhouse, & Cȏté, 2016) (Kearney et al, 2011;Porter & Kearney, 2009). For small mammals at both of our sites, T max during summer frequently exceeded the likely upper critical temperature in all three habitat types, but it was colder than the expected thermoneutral zone during winter (Araujo et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For example, neither our findings, nor studies by Selås () and Selås et al () explicitly tested interactive effects between weather covariates and forest stand characteristics (Kardell , Hertel et al ). Older forests buffer temperature variation more than more open habitats, like clearcuts, where temperature amplitudes are higher (Pigeon et al , Supplementary material Appendix 2 Fig. A10).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, brown bears in British Columbia, Canada, did not reduce their general or diurnal activity in response to increasing maximum daily temperature (McLellan and McLellan ), even though temperatures were warmer (20.4–40.1°C) than in our study area (17.4–21°C). Conversely, Pigeon et al () reported that brown bears in Alberta, Canada, where temperatures are similar to Sweden, adjusted their habitat selection and avoided clearcuts, a habitat with potentially high food availability, during the hottest part of the days. For our study area, Ordiz et al () suggested that bears primarily adjust their habitat use to avoid humans, rather than in response to warm temperatures.…”
Section: Discussionmentioning
confidence: 99%